Morphological variations of acromion process in rotator cuff tear using magnetic resonance imaging - Rashmi C Goshi; Vijay C; Vikram Patil; Chaithra N; Anupama (Journal of Krishna Institute of Medical Sciences University)
Background: The acromion is one of the markers on the posterior shoulder. The pathophysiology of Rotator Cuff Tear (RCT) seems to be related with the shape of the acromion, which is often evaluated by its characteristics. Aims and Objectives: To use magnetic resonance imaging to determine the morphological features of the acromion connected with RCT. When remedying patients with rotator cuff disease and shoulder impingement syndrome, orthopaedicians must have a thorough understanding of the structure and configuration of the acromion. To detect the RCT with respect to morphology and type of acromion. The objective was to know the incidence and type of RCT with respect to morphology and type of acromion. Material and Methods: This study, which involved 48 patients with RCT, either partial- or full-thickness, was conducted at JSS Medical College and Hospital. In our retrospective analysis, we examined the acromial type, Acromial Thickness (AT), Lateral Acromial Angle (LAA), Acromio-Humeral Distance (AHD), Critical Shoulder Angle (CSA), and Acromial Index (AI) in 48 cases of RCT. Results: The age of our participants ranged from 20 to 76 years, with mean of 40.40 years and standard deviation of 14.35 years, suggesting considerable variability in age across the study sample. AI varied between 0.11 and 0.84, with a mean of 0.58 and a standard deviation of 0.16. AT varied from 0.36 to 1.47, with a mean of 0.72 and a standard deviation of 0.19. LAA varied from 52.46 to 95.26 degrees, with a mean of 77.04 degrees and a standard deviation of 8.19 degrees. AHD varied from 0.34 to 1.24 cm, with a mean of 0.81 cm and a standard deviation of 0.18 cm. CSA varied from 10.73 to 42.82 degrees with a mean of 32.82 degrees and a standard deviation of 5.55 degrees. Conclusion: In our study, in the context of RCTs, there was no correlation between the three acromial shapes and sex, regardless of the muscle that was injured. However, we identified a significantly higher incidence of full-thickness supraspinatus tears in the right shoulders of men aged 40–60 years with type 2 acromia.